Financial Behavior of Generation Z and Millennials - Pokharel, Jhabindra; Maharjan, Isha (Journal of Emerging Management Studies, 2024)
Purpose – Managing finances and making the right financial decisions are challenging for everyone worldwide, and wrong decisions by individuals may lead the whole economic system in the wrong direction. This paper aims to investigate behavioral aspects of individuals regarding their financial decision-making. Also, it examines the moderating role of generations on behavioral aspects affecting financial decision-making,  taking into account Generation Z and Millennials.Design/methodology/approach – Kathmandu valley, the capital city of Nepal, was selected as the study area for this research. Since this study aims to analyze the financial behavior of only two generations, individuals who fall under either of these generation groups and are actively involved in financial decision-making constitute the study population. The convenience sampling technique was used within each generation group to collect data. Four hundred and thirty-eight (438) usable data were collected through a structured questionnaire and analyzed using descriptive statistics, Pearson's correlation, and hierarchical regression.Findings and Conclusion – Supporting planned behavior theory and the generation cohort theory, the findings from this analysis demonstrated a significant positive effect of digital literacy, financial literacy, financial attitude, and risk tolerance on financial behavior. At the same time, the findings of this paper also stated that ethics has a significant impact on financial behavior, which supports the cognitive and emotional biases explained by behavioral theory. Furthermore, Generation Z and Millennials significantly differ in financial literacy, attitude, and ethics, shaping their financial behavior. However, this study could not find generation moderating the effect of risk tolerance and digital literacy on financial behavior.Originality/Value - The findings of this paper contributed to the existing body of literature by validating behavioral finance and the theory of planned behavior, helping scholars gain more insights regarding the influence of financial constructs and ethics on financial behavior. Furthermore, the conclusions of this paper also validate the generation cohort theory, showing similar behavior in people of similar age or age groups. This study also explored behavioral differences between Generation Z and Millennials in Nepal, which was still to be explored.